Adsorptive performance of green-synthesized ZnO nanoparticles: RB-5 dye removal, kinetics, and antioxidant evaluation for environmental and biomedical applications - Adil Usman; Muhammad Usama Younas (Next Nanotechnology)
Nanotechnology provides significant solutions to challenges across various fields, including biomedicine, environmental remediation, and catalysis. Zinc oxide (ZnO) nanoparticles have garnered considerable attention due to their applications in biomedical and photocatalysis. This study used a green method to synthesize ZnO nanoparticles using Euphorbia granulata leaf extract. The synthesized nanoparticles demonstrated a removal efficiency of up to 94.05 % for the reactive black-5 dye at a concentration of 50 ppm over 260 min under sunlight. The maximum DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity of ZnO nanoparticles was 64.4 % at 100 µg/mL concentration. Adsorption process of biosynthesized ZnO nanoparticles was supported by kinetic (pseudo-second-order) and isotherm (Freundlich) models (R² = 0.99). This work presents an eco-friendly method for synthesizing ZnO nanoparticles and evaluating their applications in biomedical and photocatalytic fields.